Evaluating the Kisan Credit Card (KCC) Scheme: A Review of Institutional Constraints, Socio-Economic Impacts, and Policy Directions - Ali hasan; Ruqaiya bano; Bharat lal meena (The Bioscan, 2026)
The Kisan Credit Card (KCC) scheme is a vital initiative designed to provide farmers with timely and affordable access to credit, reducing their reliance on informal lending sources. Despite its importance, several institutional, financial, and socio-economic challenges such as complex application procedures, inadequate rural banking facilities, high default risks, and limited financial literacy continue to hinder its effectiveness. This review highlights major policy measures and best practices aimed at enhancing the adoption, accessibility, and efficiency of the KCC scheme. The integration of digital innovations, including online application systems, Aadhaar-based verification, mobile banking, and AI-supported credit monitoring, has simplified loan processing and strengthened financial security. Furthermore, expanding KCC eligibility to tenant farmers, sharecroppers, and women farmers has improved rural financial inclusion. Initiatives such as financial literacy programs, community-based awareness campaigns, and Financial Literacy Centers (FLCs) have also contributed significantly to educating farmers about digital banking and credit management. Although these developments mark substantial progress, continued investment in technology, policy reforms, and financial education is crucial to fully realize the potential of the KCC scheme and promote long-term financial stability and empowerment among India’s farming community. Keywords Kisan Credit Card (KCC), Financial inclusion, Digital banking, Agricultural credit, Financial literacy.